(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to identify the credit concentration and the causes of credit concentration as well as how to manage the risks of credit concentration, and methods of measuring credit concentration in the theoretical aspect of the research. Using the index (Herfindahl-Hirschman) and its reflection on capital adequacy using two indicators to measure capital adequacy, which are (ownership right to assets, ownership right to deposits), and to achieve the objectives of the research, an analysis of a sample of Iraqi private commercial banks listed In the Iraq Stock Exchange, which numbered (24) banks, (10) banks were selected from them, as financial and statistical analysis was used to test the hypotheses of the study through the programs (Excel, Spss), based on the annual reports of the banks, the research sample for the period from (2016). -2021). Among the most prominent findings of the research is that the banks in the research sample tend to focus on granting credit on specific economic activities at the expense of diversification in the credit portfolio. Also, the results of the research found that there is no relationship and effect between credit concentration and capital adequacy indicators for most of the banks in the research sample except for the banks (Al-Iktissad, Gulf, Development), as the negative effect was reversed for the (Economy) bank between credit concentration and indicators of capital adequacy, while the bank ( Gulf, Development) The effect was positive and direct between the two variables.